Novel full-thickness biomimetic corneal model for studying pathogenesis and treatment of diabetic keratopathy - Zekai Cui; Xiaoxue Li; Yiwen Ou; Xihao Sun; Jianing Gu; Chengcheng Ding; Zhexiong Yu; Yonglong Guo; Yuqin Liang; Shengru Mao; Jacey Hongjie Ma; Hon Fai Chan; et al. (Materials Today Bio)
Diabetic keratopathy (DK), a significant complication of diabetes, often leads to corneal damage and vision impairment. Effective models are essential for studying DK pathogenesis and evaluating potential therapeutic interventions. This study developed a novel biomimetic full-thickness corneal model for the first time, incorporating corneal epithelial cells, stromal cells, endothelial cells, and nerves to simulate DK conditions in vitro. By exposing the model to a high-glucose (HG) environment, the pathological characteristics of DK, including nerve bundle disintegration, compromised barrier integrity, increased inflammation, and oxidative stress, were successfully replicated. Transcriptomic analysis revealed that HG downregulated genes associated with axon and synapse formation while upregulating immune response and oxidative stress pathways, with C-C Motif Chemokine Ligand 5 (CCL5) identified as a key hub gene in DK pathogenesis. The therapeutic effects of Lycium barbarum glycopeptide (LBGP) were evaluated using this model and validated in db/db diabetic mice. LBGP promoted nerve regeneration, alleviated inflammation and oxidative stress in both in vitro and in vivo models. Notably, LBGP suppressed the expression of CCL5, highlighting its potential mechanism of action. This study establishes a robust biomimetic platform for investigating DK and other corneal diseases, and identifies LBGP as a promising therapeutic candidate for DK. These findings provide valuable insights into corneal disease mechanisms and pave the way for future translational research and clinical applications.